EXPLORATION OF STUDENTS’ MATHEMATICS LEARNING EXPERIENCES AND ENGAGEMENT OUTSIDE THE CLASSROOM - Kusmaryono, Imam; Wijayanti, Dyana (Kantor Jurnal dan Publikasi Universitas Pendidikan Indonesia, 2023)
In essence, a learning process involves students interacting with teachers, other students, and the learning environment in an educational setting. This study aimed to explore student learning experiences and the long-term impact of learning mathematics outside the classroom. This research is a longitudinal study, in which the research subjects change after a certain period of time. This study involved subjects as 208 male and female students. The author collected data through tests, questionnaires, and interview methods. The author then analyzed the data by comparing the same data over two periods. The results suggested that learning by utilizing learning resources outside the classroom in learning mathematics may help increase student engagement in the cognitive, affective, and conative dimensions. Changes shifted from learning inside classroom to learning outside classroom have created a different learning atmosphere and provided a lot of learning experiences for students, and also increased student engagement in the cognitive, affective, and conative dimensions. It indicated that learning mathematics outside the classroom has a long-term impact on student interaction in three dimensions, namely (1) the cognitive dimension; students can develop such as critical thinking, problem-solving skills, and reasoning abilities; (2) affective dimensions; students’ positive disposition towards mathematics increases while students' mathematics anxiety levels decrease; and (3) the conative dimension; such as improvement in social skills, cooperation, better communication, confidence, and diligence in learning mathematics.